2012
DOI: 10.1007/s00520-012-1583-8
|View full text |Cite
|
Sign up to set email alerts
|

Cancer caregivers’ perceptions of an exercise and nutrition program

Abstract: Findings from this study suggest that participating in an exercise- and nutrition-based intervention is viewed positively by caregivers and that the outcomes are seen as beneficial to both caregivers and survivors. Interventions that address the health needs of both members of the caregiver-survivor dyad should continue to be encouraged by allied health professionals.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
13
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 10 publications
(14 citation statements)
references
References 33 publications
1
13
0
Order By: Relevance
“…Innovative methods involving family-based nutrition education have been shown to improve health outcomes in cancer survivors' nutritional status (Molassiotis et al, 2018). Participation in exercise and nutrition programs can lead to perceived physical and benefits for survivors and caregivers (Anton et al, 2013). Technology-based intervention approaches in weight gain prevention has also improved healthy lifestyle behaviours (Lynch et al, 2019;Valle et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…Innovative methods involving family-based nutrition education have been shown to improve health outcomes in cancer survivors' nutritional status (Molassiotis et al, 2018). Participation in exercise and nutrition programs can lead to perceived physical and benefits for survivors and caregivers (Anton et al, 2013). Technology-based intervention approaches in weight gain prevention has also improved healthy lifestyle behaviours (Lynch et al, 2019;Valle et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…Dyadic healthy eating and physical activity efforts are likely to enhance involvement and overcome barriers to participation (e.g. limited independent time), while benefitting both partners (Anton et al., 2013; Falba & Sindelar, 2008; Pai et al., 2010). Health promotion programs targeted to couples have been successful in demonstrating improvement in healthy eating behaviours for cardiac patients and their partners (Yates et al., 2015) and couples showed decreased consumption of high‐fat foods, total fat and increased intake of fruits, vegetables and total fibre (Burke et al., 2003).…”
Section: Discussionmentioning
confidence: 99%
“…Prior research has found that some spousal caregivers do not enjoy exercising alone (Cao et al., 2010). In fact, many are interested in physical and leisure time activities they can engage in with their care recipients (Cao et al., 2010; van't Leven et al., 2013; Malthouse & Fox, 2014) to enhance their time together, social participation and mutual support (Anton et al., 2013). Finally, a systematic review reported that caregivers may improve both psychosocial and physical health when exercising with care recipients (Doyle et al., 2020).…”
Section: Discussionmentioning
confidence: 99%
“…A list of open-ended questions ( Table 2) was developed based on the co-authors' extensive experience with qualitative interviewing, clinical practice with cancer patients and caregivers, and in conducting exercise interventions. We also reviewed the interview questions used by Anton et al (2013) in their qualitative study of cancer family caregivers participating in an exercise programme with their care recipient. This broad-based set of questions was not used rigidly, but was a guide during the interview to allow flexibility in exploring the full range of participant experiences.…”
Section: Data Collection and Proceduresmentioning
confidence: 99%